Perkembangan Islam dan Liberalisme di Era Digital: Analisis Tafsir Maudhu’i dalam Surah Yunus Ayat 41 - Nurosidin, Ihsan; Maulana, Farhan Fatih; Aminah, Siti; Andini, Puti; Muhyi, Asep Abdul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The understanding of liberalism in people’s minds still has a narrowed meaning, without realizing the influence of liberalism is growing in life, especially in the era of swift flow of information and freedom of expression in the digital world. This research discusses the dynamics of the development of Islam and liberalism, with the analysis of maudhu’I tafsir in surah yunus verse 41 about the response of Muslims in dealing with differences in views, especially in liberalism in the digital era. This research method is qualitative using maudhu’I tafsir analysis and literature studies related to the dynamics of its development. The results of the study indicate that tolerance and the responsibility of da'wah are the answers to the problem, maudhu’I interpretation strengthens the principle without having to sacrifice the integrity of the faith. This research contributes to contemporary Islamic discourse, especially in building a narrative of religious moderation in the digital era.